Programa educativo de inteligencia artificial para mejorar la toma de decisiones estratégicas en el personal educativo del Instituto de Educación Superior Tecnológico Público Joaquín Reátegui Medina Nauta 2024 - Mozombite Inuma Denisse Tatiana (2025)
The results of a study are presented that outlined as its main objective to evaluate the effect of the artificial intelligence educational program to improve strategic decision-making in the educational staff of the Joaquín Reátegui Medina Public Technological Higher Education Institute, (IESTP) in Nauta in 2024. For this purpose, the methodological design was evaluative, field, univariate, longitudinal and quasi-experimental. The population subject to research consisted of 142 directors and teachers, of which 70 formed the sample, 35 being the experimental group and 35 being the control group. They were administered a case test previously evaluated by experts to obtain data regarding the study. The present research confirms, with statistical evidence, that the artificial intelligence educational program significantly improves strategic decision-making in the educational staff of the IESTP Joaquín Reátegui Medina. At the beginning, both groups presented mostly deficient levels; after the intervention, the experimental group showed a radical change, eliminating the deficient and regular levels, with a transition to satisfactory and excellent levels (37.1% and 62.9%, respectively). The inferential analysis revealed significant differences in the experimental group (p = .000), with a substantial increase in the central tendency values (M = 18.06 in the Posttest versus M = 7.69 in the Pretest), validating the effectiveness of the program. In conclusion, the educational program based on artificial intelligence constitutes an effective strategy to strengthen strategic decision-making in the educational field.